Culture, Health, and Science: A Multidisciplinary Liberal Arts Alternative to the Public Health Major. (January 2016) - Morgan, Lynn M.; Knight, Sabina; Gubrium, Aline C.
Since the 2003 call by the Institute of Medicine to educate undergraduates in public health, various models have emerged for incorporating public health into the liberal arts and sciences. One model is a professionalized public health major that uses core public health competencies to prepare a workforce of health professionals. A second model offers a broad-based public health major rooted in liberal arts principles, resisting the utilitarian trend toward human capital formation. A third model resists even the label of "public health, " preferring instead to introduce undergraduates to many ways of analyzing human health and healing. The multidisciplinary Culture, Health, and Science Program, based on six key commitments for preparing liberal arts students to analyze health and respond to global health challenges, is offered as an alternative to the public health major.